2021
DOI: 10.1016/j.celrep.2021.108759
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of RNA transcription during DNA replication delays duplication of transcription start sites until G2/M

Abstract: Summary As transcription and replication use DNA as substrate, conflicts between transcription and replication can occur, leading to genome instability with direct consequences for human health. To determine how the two processes are coordinated throughout S phase, we characterize both processes together at high resolution. We find that transcription occurs during DNA replication, with transcription start sites (TSSs) not fully replicated along with surrounding regions and remaining under-replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 81 publications
6
57
0
Order By: Relevance
“…
Figure 1 FACS analysis of S-phase progression following cells synchronization by serum starvation The top panel showing the FACS results using propidium iodide (PI) and BrdU after serum starvation (0 h) (bottom left, G0/G1 phase; top, S phase; bottom right, G2 phase); the bottom panel showing the quantification of cells in each stage; n = 3; average mean +/− standard error of the mean. (Adapted from Wang et al. 2021 ).
…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…
Figure 1 FACS analysis of S-phase progression following cells synchronization by serum starvation The top panel showing the FACS results using propidium iodide (PI) and BrdU after serum starvation (0 h) (bottom left, G0/G1 phase; top, S phase; bottom right, G2 phase); the bottom panel showing the quantification of cells in each stage; n = 3; average mean +/− standard error of the mean. (Adapted from Wang et al. 2021 ).
…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Cells that are both in G2 by DNA content and pS10-H3 positive (highlighted in the box) are sorted followed by BrdU sequencing. (Adapted from Wang et al. 2021 ).…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the relative locations of these elements along eukaryotic chromosomes are not random, but efficiently firing replication origins tend to overlap with transcription start sites (TSSs) of highly transcribed genes, thereby promoting a global CD bias of transcription and replication [ 10 , 11 ]. Although this strategy can effectively minimize HO-TRCs, considered to be the more harmful and deleterious type of TRC in bacteria, yeast and higher eukaryotes [ 12 , 13 , 14 , 15 ], a recent study showed that a subset of TSSs remains under-replicated and relies on G2/M DNA synthesis (G-MiDS) to complete replication and prevent DNA damage in mitosis [ 16 ]. These G-MiDS hotspots remain persistently under-replicated in the S-phase due to RNAP complexes at the TSS that block replication fork progression.…”
Section: Introductionmentioning
confidence: 99%